Genotoxicity and oxidative stress induced by sediments from the Sado Estuary and potential antimutagenic effects of quercetin - Pinto, Miguel (2013)
The Sado Estuary is affected by various sources of pollution, such heavy-industry, urbanism, mining, agriculture and maritime traffic and sizable amounts of organic and inorganic contaminants were identified in the sediments. These compounds can be accumulated in the edible parts of estuarine species and agricultural products, thus entering the human food chain and posing a public health problem. This study had two objectives: i) to study genotoxic effects of sediments from the Sado Estuary in a human liver-derived cell line; and ii) to analyze oxidative DNA damage (produced by the same samples) and try to reverse it by treatment with quercetin, as an antioxidant. Sediments were collected from four distinct sites of the Sado Estuary: Sites P and C from the northern area and sites A and E from the southern area. Contaminants were extracted with dichloromethane:methanol (2:1) and genotoxicity was evaluated by the comet assay; oxidative damage was quantified using the DNA repair endonuclease FPG-modified comet assay. HepG2 cells were exposed (48h) to concentrations of each extract (10 - 200 mg SEQ/ml). To confirm oxidative stress, cells were co-exposed for 48h to the concentrations of each extract that were able to produce oxidative DNA damage. A significant increase in total DNA strand breakage was observed following cells exposure to extract P (with and without FPG). Significant DNA damage was only observed following FPG treatment for extracts E and A, suggesting induction of oxidative DNA damage. Extract C failed to induce genotoxicity. Co-exposure to quercetin did not reverse the observed oxidative DNA damage, but rather increased it, suggesting a possible co-mutagenicity. The differential genotoxicity observed in samples from the northern (P) and southern areas (E and A) of the Sado Estuary probably reflects different pressures from an industrialized and urban area versus an agricultural area, respectively.